PENGARUH PERMAINAN PAPER CLAY TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI PAUD DOA IBU - A. Sri Wahyuni Asti; Jein Jein; Rusmayadi (STKIP Subang, 2024)
This study aims to determine whether or not there is an effect of paper clay games on the fine motor skills of children aged 4-5 years at PAUD Doa Ibu before and after being treated. The research approach used is a quantitative approach with the type of research Quasi Experiment Design. The independent variable in this study is the paper clay game and the dependent variable in this study is fine motor skills. The population in this study were 16 children. Sampling in this study using purposive sampling. The sample in this study were 16 children, 8 children as the control group and 8 children as the experimental group. The data analysis technique used is descriptive statistical analysis and non-parametric statistical analysis. Based on the results of the study, it can be concluded that the fine motor skills of children who have been given paper clay games in the experimental group are better than the control group. The results of data analysis obtained an average increase in the experimental group of 9.5 while in the control group 3.26 and the test results showed a sig. (2-tailet) 0.011 <0.05, then H0 is rejected and H1 is accepted, this proves that paper clay games have a significant effect on the fine motor skills of children aged 4-5 years at PAUD Doa Ibu.